Margin verification for hypofractionated prostate radiotherapy using a novel dose accumulation workflow and iterative CBCT. (September 2020) - Studenski, Matthew T.; Delgadillo, Rodrigo; Xu, Yihang; Both, Joseph; Padgett, Kyle; Abramowitz, Matthew; Ford, John C.; Dal Pra, Alan; Pollack, Alan; Dogan, Nesrin
Highlights: Daily iterative CBCT is a viable modality for automated dose accumulation. Iterative CBCT provides superior deformable registrations compared to standard CBCT. 5 mm prostate margins (3 mm posterior) are adequate in hypofractionated courses. Intra-prostatic lesions require a margin to ensure full coverage. Abstract: Purpose: Hypofractionated radiotherapy for prostate cancer reduces the inconvenience of an extended treatment course but the appropriate treatment margin to ensure tumor control while minimizing toxicity is not standardized. Using a novel dose accumulation workflow with iterative CBCT (iCBCT) images, we were able to validate treatment margins. Methods: Sixteen patients treated to the prostate on a hypofractionated clinical trial were selected. Prescription dose was 3625 cGy to > 95% of the PTV in 5 fractions with a boost to 4000 cGy to the high risk GTV (if applicable). PTV margin expansion was 5 mm isotropic except 3 mm posterior, no margin for the GTV. Daily iCBCT images were obtained while practicing strict bladder and rectal filling protocols. Using a novel adaptive dose accumulation workflow, synthetic CTs were created and the daily delivered dose was recalculated. The daily dose distributions were accumulated and target coverage and organ dose were assessed. Results: Although the PTV coverage dropped for the accumulated dose, the prostate coverage was not compromised. The differences in bladder and anorectum dose were not significantly different. Four patients received a boost to the GTV and a significant decrease in coverage was noted in the accumulated dose. Conclusions: The novel dose accumulation workflow demonstrated that daily iCBCT images can be used for dose accumulation. We found that our clinical treatment margins resulted in adequate dose to the prostate while sparing OARs. If the goal is to deliver the full dose to an intra-prostatic GTV, a margin may be appropriate.